Molecular nanomagnets - Gatteschi, D. (Dante); Sessoli, Roberta; Villain, Jacques; Oxford University Press (Oxford ; New York : Oxford University Press, 2006)
"Nanomagnetism is a rapidly expanding area of research which appears to be able to provide novel applications. Magnetic molecules are at the very bottom of the possible size of nanomagnets and they provide a unique opportunity to observe the coexistence of classical and quantum properties. The discovery in the early 90's that a cluster comprising twelve manganese ions shows hysteresis of molecular origin, and later proved evidence of quantum effects, opened a new research area which is still flourishing through the collaboration of chemists and physicists." "This book is the first attempt to cover in detail the new area of molecular nanomagnetism, for which no other book is available. In fact research and review articles, and book chapters are the only tools available for newcomers and the experts in the field. It is written by the chemists originators and by a theorist who has been one of the protagonists of the development of the field, and is explicitly addressed to an audience of chemists and physicists, aiming to use a language suitable for the two communities."--BOOK JACKET.
Introduction -- Magnetic interactions in molecular systems -- Observation of microscopic magnetism -- Single-molecule magnets -- Thermally activated magnetic relaxation -- Magnetic tunnelling of an isolated spin -- Introduction to path integrals -- Tunnelling in a time-dependent magnetic field at low temperature -- Interaction of a spin with the external world at low temperature -- Tunnelling between excited states -- Coherence and decoherence -- Disorder and magnetic tunnelling -- More experiments on single-molecule magnets -- Other magnetic molecules -- Emerging trends in molecular nanomagnetism.
Includes bibliographical references (pages [363]-387) and index.
Mode of access: World Wide Web.
Keywords: Magnetism; Nanostructured materials -- Magnetic properties